Hydroxychloroquine treatment in COVID‐19: A descriptive observational analysis of 30 cases from a single center in Wuhan, China. Issue 11 (16th August 2020) - Xue, Huiying; Liu, Yi; Luo, Pan; Liu, Xiulan; Qiu, Lin; Liu, Dong; Li, Juan
Abstract: Hydroxychloroquine (HCQ) garnered scientific attention in early February following publication of reports showing in vitro activity of chloroquine (CQ) against coronavirus disease 2019 (COVID‐19). While studies are mixed on this topic, the therapeutic effect of HCQ or CQ still need more valid clinical evidence. In this descriptive observational study, we aimed to discuss the treatment response of HCQ in COVID‐19 infected patients and 30 cases were included. The demographic, treatment, laboratory parameters of C‐reactive protein (CRP) and interleukin‐6 (IL‐6) before and after HCQ therapy and clinical outcome in the 30 patients with COVID‐19 were assessed. To evaluate the effect of mediation time point, we also divided these cases into two groups, patients began administrated with HCQ within 7 days hospital (defined as early delivery group) and 7 days after hospital (defined as later delivery group). We found that, the elevated IL‐6, a risk factor in severe patients were reduced to normal level after HCQ treatment. More importantly, patients treated with HCQ at the time of early hospital recovered faster than those who treated later or taken as second line choose for their obvious shorter hospitalization time. In summary, early use of HCQ was better than later use and the effect of IL‐6 and CRP level cannot be ruled out.